Antinomy of Biological Father's Liability to Out-of-Marriage Children in Notary Deed: Antinomi Pertanggungjawaban Ayah Biologis Terhadap Anak Luar Kawin dalam Akta Notaris - Yohanes, Joshua; Djaja, Benny (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
Constitutional Court Decision Number 46/PUU-VIII/2010 impacts the position of a child out of wedlock. With the enactment of the decision, a legal relationship arises between the child out of wedlock and his biological father. This article discusses the position of children out of wedlock after the decision is made and how the decision is applied in a notarial deed. The method used in this study is the normative legal method, in which research analyzes norms, laws, regulations, and legal theory related to applying the abovementioned decisions in the context of civil relations of illegitimate children in a notarial deed. Constitutional Court Decision Number 46/PUU-VIII/2010 shows that it cannot be directly applied as a basis for kinship relations between illegitimate children and their fathers. However, this relationship can be recognized through a court decision taking into account science and technology and other relevant evidence.